Las remuneraciones devengadas en un proceso de amparo: Casación Laboral 992-2012-Arequipa, 09/03/2012 - Pacheco Zerga, Luz (Revista de Derecho, 2020)
This article analyzes the legal nature of private dismissal legally, either constitutional or statutory seat and the consequences that follow in relation to wages or compensation earned, which are recognized by comparative law, but denied by the Supreme Court in its recent judgments.